Duodenoduodenostomy for obstruction of the sigmoid flexure of the duodenum in cattle. Issue 5 (15th May 2018) - Hackett, Eileen S.; Lang, Hayley M.; Desrochers, Andre; Nichols, Sylvain; Fubini, Susan Lawson
Abstract: Objective: To describe clinical findings, surgical treatment, and outcome associated with duodenoduodenostomy for treatment of duodenal obstruction secondary to adhesions associated with the sigmoid flexure of the duodenum. Study design: Retrospective study (1996‐2016). Animals: Fourteen Holstein cattle. Methods: Medical records of cows treated at 3 academic surgical referral centers with duodenoduodenostomy for duodenal obstruction secondary to adhesions associated with the sigmoid flexure of the duodenum were reviewed. Data that were collected included signalment, physical examination results, laboratory results, diagnostic findings, treatments, and survival to discharge. Owners were contacted for follow‐up information. Results: Affected cattle ranged in age from 4 months to 5 years. Electrolyte abnormalities, including severe hypochloremia, were present in all cases. Abnormalities included cranial duodenal distension without concurrent distension of the descending duodenum and palpable focal adhesions in the region of the sigmoid flexure of the duodenum. Duodenoduodenostomy involved a stapled (n = 11) or sutured (n = 3) side‐to‐side anastomosis between the cranial duodenum and descending duodenum. Thirteen of 14 cattle that were treated with duodenoduodenostomy survived to hospital discharge. Long‐term follow‐up was available in 8 cows, and 7 of those 8 survived for at least 1 year. Conclusion: Short‐ and long‐term survival were favorable after duodenoduodenostomy in cattle with adhesions associated with the sigmoid flexure of the duodenum. Clinical significance: Duodenoduodenostomy results in acceptable survival and future productivity in cows with obstruction at the sigmoid flexure of the duodenum.